Comparison Between The Combination Of Three Steps Rhythm Training And Alternating Phase With Dead Leg And Mini Hurdles Progression Exercise Combinations To Running Speed And Accuracy Through Gawang Kanga's Escape (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
Kids athletics is a type of child sports designed in such a way based on the study of sports science so that it can support all biomotor components that support physical fitness. The purpose of this study was to determine the difference between the results of a combination of three-step rhythm and alternating phase training with a combination of dead leg training and mini hurdles progression to the speed and accuracy of Kanga's Escape. The experimental method aims to compare 2 training methods for Dead Leg and Mini Hurdles Progression Training with Three Steps Rhythm and Alternating Phase Exercises on Running Speed and Accuracy of Passing Kanga's Escape Goal. The division into two groups was obtained from the results of matching the average scores of the subjects from the initial test so that the two groups departed from the same starting point. The measurement scale in this study is a numerical scale, so the data normality test must be done first with a significance level of 5%. The data normality test used was Shapiro-Wilk because the number of samples was less than 50. The results showed that there was a big difference in the combination of Dead Leg Training and Mini Hurdles Progression with Three Steps Rhythm and Alternating Phase Exercises on the Running Speed and Accuracy of Passing the Kanga's Escape Goal. Seeing the results of the data, it shows that the Three Steps Rhythm and Alternating Phase training method shows a value of at least 0.082 sig from the data for the Dead Leg and Mini Hurdles Progression Exercise method of 0.134 sig. In the P test, 14% and 86% of the data are 11% and 32%, while in the homogeneous test the data shows homogeneity than the Dead Leg Training Method and Mini Hurdles Progression. So this research tends to be better off using the Three Steps Rhythm and Alternating Phase training method. The conclusion above shows that there is an effect in the combination of Dead Leg and Mini Hurdles Progression training with Three Steps Rhythm and Alternating Phase Exercises on the Running Speed and Accuracy of Passing the Kanga's Escape Goal which has a better tendency to use a combination of Three Steps Rhythm and Alternating Phase exercises to achieve an increase. significant or good.